The message of discipleship : authentic followers of Jesus in today's world - Morden, Peter J. (Bible speaks today., 2018)
Soon after Jesus began his public ministry, he called his first "disciples." He would teach and train them and then, after his death and resurrection, commission and empower them to go to the "nations" to make more "followers" of himself. The risen Jesus is still calling and sending disciples today. If we heed his call the result can be just as transformative and as exciting as it was for the first disciples. While there are no explicit occurrences of the term "disciple" outside the Gospels and Acts, with only two further biblical references to "followers" of Jesus, it is Peter Morden's conviction that we need the whole Bible if we are going to be whole-life disciples. He reflects on Scripture and asks the primary question, "How do we live as committed disciples of Jesus today?" He explores the foundations, the resources and the practice of discipleship, from a range of Old and New Testament texts. The result is a well-rounded and satisfying picture of Christian discipleship, one that is wonderfully attractive as well as deeply challenging.